(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Increased population has resulted in a rise in demand for commodities, resulting in fast industrialization. The generation of industrial waste has increased as a consequence of the development of industrial settings. These industrial pollutants affect the environment by polluting the water, air, and soil. Non-biodegradable wastes, such as poisonous chemicals, pesticides, plastics, or other non-biodegradable compounds, as well as biodegradable molecules, such as paper, leather, or wool, may be included. Toxics, reactive industrial effluent, carcinogenic industrial effluent, and ignitable industrial effluent are all possibilities. As a result, throwing trash into bodies of water without proper treatment or management might have severe environmental and health implications. In wastewater, some waterborne illnesses flourish, releasing chemicals that is harmful to human health and the environment. Acute toxicity, inflammatory diseases, or reproductive failure are all caused by chemicals found in industrial effluent. To address the health or environmental problems generated by chemical sewage water, it is critical to eliminate its toxicity by proper chemical, physical, or biological treatment so that it may be recycled to save water.